БАНКІВСЬКЕ КРЕДИТУВАННЯ В ОБЛІКОВІЙ ПОЛІТИЦІ ЗЕМЛЕКОРИСТУВАЧІВ АГРАРНОГО СЕКТОРУ ЕКОНОМІКИ УКРАЇНИ (ІННОВАЦІЙНА ЕКОНОМІКА, 2022)
Левандівський О.Т., Черневий Ю.І., Баланюк І.Ф., Свиноус І.В.  БАНКІВСЬКЕ КРЕДИТУВАННЯ В ОБЛІКОВІЙ ПОЛІТИЦІ ЗЕМЛЕКОРИСТУВАЧІВ АГРАРНОГО СЕКТОРУ ЕКОНОМІКИ УКРАЇНИМета. Вивчення особливостей та стану банківського кредитування землекористувачів в аграрному секторі, а також перспектив його подальшого розвитку.Методика дослідження. Методологічною основою дослідження стали нормативно-правові акти, праці вітчизняних і зарубіжних учених із питань банківського кредитування та державної підтримки землекористувачів в аграрному секторі економіки України. У процесі дослідження використано такі основні методи: системно-структурний та абстрактно-логічний (для теоретичних узагальнень результатів аналітичних розрахунків і формулювання висновків); аналізу і синтезу (для деталізації об’єкта дослідження через його поділ на окремі складові та зведення результатів їх вивчення в одне ціле); метод порівняльного аналізу (для обґрунтування застосування окремих інструментів регулювання виробничих і управлінських відносин); економіко-статистичний – групування, кореляційно-регресійний аналіз (для виявлення впливу чинників на окремі його критерії); розрахунково-конструктивний (в опрацюванні стратегії розвитку).Результати дослідження. Розглянуто передумови фінансово-кредитного забезпечення землекористувачів. Наведено стримуючі чинники ефективного функціонування банківського кредитування у аграрному секторі. Розкрито особливості державної підтримки землекористувачів. Показано рівень ефективності банківського кредитування та державної підтримки сільськогосподарських товаровиробників. Виділено переваги та проблеми, пов’язані із фінансовим забезпеченням. Досліджено зарубіжний досвід фінансової підтримки землекористувачів.Наукова новизна результатів дослідження. Обґрунтовано залежність землекористувачів від державної підтримки. Розкрито залежність між рентабельністю і банківським кредитуванням землекористувачів в аграрному секторі економіки України.Практична значущість результатів дослідження. Впровадження розроблених пропозицій дасть змогу активізувати розвиток землекористувачів в аграрному секторі економіки України. Завдяки банківському кредитуванню і державній підтримці вони отримають очевидні переваги.Ключові слова: банківське кредитування, державна підтримка землекористувачі, аграрний сектор економіки УкраїниLevandivskyi O.T., Chernevyі Yu.I., Balaniuk I.F., Svynous I.V. BANK LENDING IN THE ACCOUNTING POLICY OF LAND USERS OF THE AGRICULTURAL SECTOR OF THE ECONOMY OF UKRAINEPurpose. The aim of the article is to study the features and state of bank lending to land users in the agricultural sector, as well as prospects for its further development.Methodology of research. The methodological basis of the study were regulations, works of domestic and foreign scholars on bank lending and state support of land users in the agricultural sector of Ukraine. The following methods were system-structural, abstract and logical (for theoretical generalizations of the results of analytical calculations and formulation of conclusions), analysis and synthesis (to detail the object of study through its division into individual components and summarizing the results of their study into one whole); method of comparative analysis (substantiate the use of certain tools to regulate production and management relations); economic and statistical – grouping, correlation-regression analysis (to identify the influence of factors on some of its criteria); calculation and constructive (in the development of development strategy). Achieving this goal has led to the following tasks: to assess the current state of bank lending to land users, to determine the features of bank lending to land users and to suggest the main directions of improving bank lending. The main methods of this study are the dialectical method, the system method, the method of comparison, methods of analysis and synthesis, economic and statistical methods, tabular and graphical methods, the method of generalization.Findings. Prerequisites for financial and credit support of land users are considered. The restraining factors of effective functioning of bank lending in the agricultural sector are given. Features of state support of land users are revealed. The level of efficiency of bank lending and state support of agricultural producers is shown. The advantages and problems related to financial security are highlighted. Foreign experience of financial support of land users is studied.Originality. The dependence of land users on state support is substantiated. The relationship between profitability and bank lending to land users in the agricultural sector of Ukraine is revealed.Practical value. The implementation of the developed proposals will allow to intensify the development of land users in the agricultural sector of Ukraine's economy. Thanks to bank lending and government support, they will gain obvious benefits.Key words: bank lending, state support to land users, agricultural sector of Ukraine 's economy.